Advanced adsorption-based osmotic heat engines with heat recovery for low grade heat recovery. (November 2021) - Zhao, Yanan; Li, Mingliang; Long, Rui; Liu, Zhichun; Liu, Wei
Abstract: Efficiently utilizing the low-grade heat contributes to improving energy consumption structure and energy utilization efficiency, as well as preventing environmental deterioration. To harvest low-grade heat below 80 °C, advanced adsorption-based osmotic heat engines are constructed, which consist of an adsorption-based desalination module for thermally separating the salt solution into concentrated and diluted streams, and a reverse electrodialysis module for converting produced salinity gradient into electricity. Two different heat recovery configurations are employed to improve the heat-to-electricity performance: one is that the cooling power generated in the evaporator is used to cool the condenser and the other is that evaporator is coupled inside the condenser. The transient responses are analyzed and the effects of adsorption/desorption time, switching time, working concentration and heat source temperature on the heat-to-electricity performance are discussed. The efficiency with respect to Carnot efficiency is also presented to provide information on effectively utilized level of the available exergy. Compared with original configuration, the reduced effective condensing temperature in Configuration I and the pressurization effect in Configuration II significantly elevate the working capacity, thus to boost the work extracted. At lower working concentrations and adsorption times, the electric efficiency can be improved via Configuration II, while at higher working concentrations and adsorption times, the advanced configurations hinder the electrical efficiency. In Configuration II, compared with original configuration, the electric power and efficiency are improved by 68.3% and 15.2%, respectively, at a heat source temperature of 333.15 K with 2 mol/kg NaCl solution. While with 7 mol/kg NaCl solution, the electric power is augmented by 11.8% while the electric efficiency is decreased by 19.8%. This study may contribute to designing advanced adsorption-based osmotic heat engines to achieve an upgraded heat-to-electricity performance.